AKURASI ARAH KIBLAT MASJID DI KOTA METRO - Jamil, A. (JURNAL TAPIS, 2011)
The direction of Qibla that is objected by Kaâbah in Mecca. It is obligated to Moslem to do their worship, such as prayer, tawaf, and corpse funeral. Mosque, the prayer place, must be measured in accordance with the right direction of Qibla. So that, it can properly leads to the direction of Qibla in accordance with the Syariah rules. Like the reality in Solo, Yogyakarta, Bandung and Jakarta, there are still many mosques which is not correctly head to the direction of Qibla in Metro city. The main problem of this research is how is the accuracy of Mosquesâ Qibla direction in Metro city?. This research is aimed in describing the accuracy of Mosquesâ Qibla direction in Metro city. This is a descriptive qualitative research. The object of this research is mosques in Metro city, with using purposive proportional sampling. The data were collected by observation and measurement, with special tool, GPS. The researcher analyzed the data qualitatively. The average deviation of Qibla direction on West Metro is the lowest deviation, namely 7 degrees. East Metro has 9 degrees in average, and Central Metro has 10 degrees. While North Metro and South Metro has the highest deviation, between 16-17 degrees.Â Keywords: Akurasi Arah Kiblat, Masjid, Kota Metro